The Effect of Processing Parameters on the Properties of Fish Gelatin Hydrolysate Nanoparticle - Subara, Deni; Jaswir, Irwandi (Institut Teknologi Sumatera, 2021)
Fish gelatin hydrolysate is a well- known fish by-product that is high in protein content. It is produced from by-product waste from the fish processing industry, which includes fish skin, head, and bones. Gelatin hydrolysates have recently received much attention due to its high protein content and bioactivity, which includes antioxidant, antimicrobial and antihypertensive activities. The transformation of gelatin hydrolysate into nanoparticles is believed to increase its economic value. Furthermore, reduction into nano-size increases the absorption characteristic of this material. Here, fish gelatin hydrolysate nanoparticles are prepared for the first time using desolvation method. The effects of concentration of gelatin hydrolysate, pH of solution, and acetone concentration on nanoparticle size are determined. The prepared gelatin hydrolysate nanoparticles were found to have spherical shape with sizes varying from 300-400 nm with a mean size of 408 ± 11.4 nm, zeta potential of -16.4 ± 1.2 mV and PDI 0.203 ± 0.07. This study showed that concentration of gelatin hydrolysate, pH and concentration of solvent have significant effects on nanoparticle size. The gelatin hydrolysate nanoparticles can be applied in the pharmaceutical industry for the encapsulation of drugs to facilitate delivery to target sites.